Use of external fixator pre- and post-reconstruction in the multiligament injured knee - Lucidi, Gian Andrea; Grassi, Alberto; Cucurnia, Ilaria; Macchiarola, Luca; Zaffagnini, Stefano (Annals of Joint; Vol 3 (September 2018): Annals of Joint, 2018)
Multiligament knee injury (MLKIs) is a rare condition, making up the 0.02% of the orthopedic injuries, but are potentially devastating to patients. The management of such lesions mandates a clear knowledge of the anatomy on all sides of the joint.